1980
DOI: 10.1002/eji.1830100217
|View full text |Cite
|
Sign up to set email alerts
|

Absence of an antigen‐specific helper T cell required for the expression of the Tn 15 idiotype in mice treated with anti‐μ antibody

Abstract: T‐dependent anti‐phosphorylcholine (PC) plaque‐forming cell (PFC) responses were studied in BALB/c mice. Helper T cells derived from normal, carrier‐primed donors induced anti‐PC PFC responses dominated by the T15 idiotype. Helper T cells derived from carrier‐primed mice that had been treated from birth with anti‐μ antibody, so that they were lacking B cells and circulating antibody bearing the T15 idiotype, also provided helper cell function for the anti‐PC antibody response. In contrast to the response induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
0

Year Published

1980
1980
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 15 publications
7
61
0
Order By: Relevance
“…It has been previously established that the dominant production of T 15 idiotype in the antibody response to PC-proteins requires two distinct Th (11,12). One Th cell set is present in both carrier-primed normal mice and mice treated from birth with anti-/z antibody.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been previously established that the dominant production of T 15 idiotype in the antibody response to PC-proteins requires two distinct Th (11,12). One Th cell set is present in both carrier-primed normal mice and mice treated from birth with anti-/z antibody.…”
Section: Resultsmentioning
confidence: 99%
“…The second Th set is present in normal BALB/c mice but lacking in carrier-primed anti-/z suppressed mice, and it is necessary for predominant production of the T15 idiotype. The missing T cell set necessary for T15 production in anti-/t suppressed BALB/c mice can be restored by adding carrier-primed T cells from normal BALB/c donors along with the priming antigen (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, Bottomly et al (11) have shown that treatment of newborn mice with anti-# antibody leads to the disappearance of not only sIg + B lymphocytes but also an antigen-specific T helper cell required for the expression of the T15 idiotype. Similarly, studies by Fultz and co-workers (23) have indicated that chronic suppression of an IA k specificity results in the depletion of surface IgM + B lymphocytes as well as significantly decreased MLR responses.…”
Section: Discussionmentioning
confidence: 99%
“…Mice were injected intraperitoneally with 10 /Lg antibody within 24 h of birth. Injections were continued at 48 -h intervals until the mice were killed between days 35 and 45, mimicking the protocol used to deplete/l-bearing B cells (2,11).…”
Section: Methodsmentioning
confidence: 99%